Os desafios da diversidade cultural para e na formação de professores/as do curso de Pedagogia da Faculdade de Educação da Universidade Federal do Amazonas - Mendonça, Yasmim Santarém (Brasil, 2022)
This article discusses the training of teachers in the Pedagogy course at the Federal University of Amazonas, analyzing the challenges of/in teaching practice and teaching from the axis of cultural diversity in the Amazonian context. Its general objective is to identify the challenges of cultural diversity for and in the training of teachers, seeking to understand the study of the subject in the context of graduation. And as specific objectives: a) to search the literature for elements that support the aforementioned study; b) gather testimonies/experiences that further highlight the relevance of teaching work in teacher education linked to the theme of cultural diversity; and c) identify in the curriculum of the Degree in Pedagogy at UFAM the disciplines that enhance the work with cultural diversity in order to verify the frequency with which they are offered. This qualitative work was developed from the bibliographic research allied to the questionnaire technique for data collection. The results achieved express the need for a more solid school education, in terms of reading and research for future university students; of closer approximation with the regional culture by the professors so that they can insert even more in their practices related to diversity. The study, finally, emphasizes that the number of subjects in the curriculum is not the core of the issue, but the planning and willingness to make this approximation - the diversity of cultures - in the different disciplines.